ANALISIS BERPIKIR KRITIS MATEMATIKADALAM MENYELESAIKAN SOAL MATEMATIKA BAGI SISWA DENGAN KEMAMPUAN RENDAH MELALUI METODE REWARD AND PUNISHMENT DI SMA NEGERI 1 BATANG ANGKOLA - masdelima azizah Sormin; Lisna Agustina; Nur Sahara (Universitas Muhammadiyah Tapanuli Selatan, 2018)
AbstractThis study aims to determine: the influence of students' mathematical critical thinking analysis in solving mathematical problems through the reward and punishment method in SMA Negeri 1 Batang Angkola. The type of research used is quasi-experiment with pre-test-post-test control group design. The population in this study consisted of all class X students of SMA Negeri 1 Batang Angkola, while the sample consisted of 20 students in class X-1 as an experimental class and 20 students in class X-2 as a control class. Sampling is done through purpose sampling technique. The research instrument used was a test of students' mathematical critical thinking skills. Statistical hypothesis testing in this study used the t test. The effect of the ability of mathematical critical thinking students who get learning with reward and punishment learning is higher than students who get regular learning. With the results of the calculation obtained, then t count = 1.85 and at the level of α = 0.05 and dk = 20 + 20 - 2 = 38 then obtained t table = 1.54. Thus it is concluded that tcount> t table or 1.85> 1.54, so Ha is accepted and H0 is rejected. This shows that students' critical mathematical thinking is good enough. With reward and punishment learning makes students more active, enthusiastic and independent. This means that the influence of critical thinking in mathematics mathematics learning of students towards reward and punishment learning is better than students' critical thinking of mathematics by using ordinary learning in class X of SMA Negeri 1 Batang Angkola. Keywords: Critical Thinking, Reward and Punishment, Mathematical Problems